Sexuality, quality of life and psychological well-being in older adults: A correlational study - Nur Elçin Boyacıoğlu; Fahriye Oflaz; Aysu Yıldız Karaahmet; Buse Kübra Hodaeı; Yasin Afşin; Semra Erpolat Taşabat (Elsevier, 2023)
Objective: This study aimed at analyzing the relationship between general health status, quality of life, and sexual life among older adults. Study design: This descriptive-correlational design study was conducted with the participation of 323 (169 female and 154 male) older people at the age of 65 + . The participants were clients of the outpatient services in a general hospital in Istanbul. Data were collected with the General Health Questionnaire, Arizona Sexual Experiences Scale, and Quality of Life Scale. Results: Psychological well-being had no association with sexuality scores whereas quality of life had a significant association. Older people with better quality of life had less sexual dysfunctionality. Participants who were up the 75 years old, who have lower education, lower economic status, unemployed, having chronic diseases seemed to experience higher ASEX scores, meaning that higher sexual dysfunction, lower GHQ scores and lower quality of life level. Conclusions: Sexuality in older people changes over time and continues to hold its importance. Less sexual dysfunction seemed to relate with higher quality of life in older people. Researchers should consider the importance of the quality of life on sexual satisfaction in older people.